Entrepreneurs and Artists in the Time of COVID-19 - Youth Employment Services (YES) (2020)
In response to the detrimental effects of COVID-19, Canadian governmental agencies and other organizations have deployed multiple programs to support local entrepreneurs and their businesses. In the current evolving situation, it’s hard to know where to turn. This document contains some of the currently available programs and resources for entrepreneurs and will be updated periodically. Last updated on July 27, 2020.

The 19th Annual Entrepreneurship Conference - Youth Employment Services (YES)